1983
DOI: 10.1001/archinte.143.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilus endocarditis. Two patients with complications

Abstract: Two cases of Hemophilus endocarditis were diagnosed in our hospital during a six-month period. Although both patients were in good health until the onset of their endocarditis, both had brain emboli and required emergency heart-valve surgery. Falsely low incidences of this disease have been reported, since Hemophilus sp are difficult to isolate. Additionally, these organisms are consistently associated with large vegetations and have a greater than 50% incidence of embolization. It is this higher incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The focus of infection and the clinical symptoms were similar to those described in the literature (15,16,23,(27)(28)(29)(30)(31), with pneumonia being most frequent. Haemophilus influenzae causes between 1 and 4 % of all cases of meningitis in adults (32,33).…”
Section: Discussionsupporting
confidence: 79%
“…The focus of infection and the clinical symptoms were similar to those described in the literature (15,16,23,(27)(28)(29)(30)(31), with pneumonia being most frequent. Haemophilus influenzae causes between 1 and 4 % of all cases of meningitis in adults (32,33).…”
Section: Discussionsupporting
confidence: 79%
“…These cases typically have large vegetations with embolie complications and require surgery for cure. 16 Three patients, two with pneumonia and one with epi¬ glottitis, experienced symptomatic H influenzae conjuncti¬ vitis accompanying their primary disease. In all cases conjunctivitis was cured with systemic antibiotic and top¬ ical sulfacetamide sodium therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Early diagnosis of //. parainfluenzae endocarditis is best es tablished by echocardiography, as large vege tations are typical for Haemophilus species [2,5], We propose that echocardiography should be performed in patients with fever of unknown origin whose blood cultures are negative. Valve resection was done in pa tients with persistent infection although se vere heart failure is uncommon in Haemo philus endocarditis involving the tricuspid or pulmonary valve.…”
Section: Discussionmentioning
confidence: 99%
“…Endocarditis caused by the Haemophilus species is considered to be very uncommon [1], Appropriate antibacterial therapy using in vitro tests is sometimes inadequate, and valve resection has had to be performed in some cases because of persisting infection [2,5]. A review of Haemophilus endocarditis covering a period of 50 years revealed 68 documented cases [2], In 42 cases Haemophi lus parainfluenzae was found to be the causa tive pathogen of endocarditis.…”
mentioning
confidence: 99%
See 1 more Smart Citation